LEVERAGING INITIAL CAPITAL AND INCOME THROUGH HR-DRIVEN INNOVATION: STRENGTHENING HUMAN RESOURCE MANAGEMENT EFFECTIVENESS IN MSMES - Dinna Dewi, Almas Farah; Agustiyaningsih, Dea Nova; Handriyono; Fadah, Isti (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2025)
This study explores how initial capital, when strategically utilized through HR-driven innovation, enhances the effectiveness of human resource management (HRM) in Micro, Small, and Medium Enterprises (MSMEs). Drawing on data from 155 MSMEs and using multiple regression analysis, the findings reveal that both initial capital and HR-driven innovation significantly influence HRM effectiveness, particularly in areas such as talent development, employee motivation, and organizational adaptability. The interaction between initial capital and innovation indicates that financial readiness, when aligned with innovative HR practices, amplifies the capacity of MSMEs to manage and retain human capital effectively. Meanwhile, other variables such as age, number of dependents, working hours, business duration, monthly capital, monthly personal expenditure, education, marital status, and domicile showed no significant impact. These results underscore the importance of integrating financial strategy with human resource innovation to promote sustainable business growth.